1999
DOI: 10.1177/001979399905200405
|View full text |Cite
|
Sign up to set email alerts
|

What is a Promotion?

Abstract: Using National Longitudinal Survey of Youth data, the authors analyze the determinants and consequences of a promotion among young workers. Most events that workers called "promotions" involved no change in position or duties, but were simply an upgrade of the current position. Typically, only one person was considered for the promotion. Men were more likely to be promoted than women, and whites more likely than blacks or Hispanics. The acquisition of company training and the receipt of a prior promotion were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 30 publications
2
48
1
Order By: Relevance
“…An example is the preferences in promotion given to younger workers in some firms (Rosen and Jerdee, 1977). While Rosen and Jerdee did not present evidence of a negative outcome that results from this practice, Pergamit and Veum (1999) showed that there are many positive consequences of promotion, such as an increase in supervisory responsibilities and the receipt of additional training. Other work has shown symptoms of age discrimination in labor markets.…”
Section: Historymentioning
confidence: 91%
“…An example is the preferences in promotion given to younger workers in some firms (Rosen and Jerdee, 1977). While Rosen and Jerdee did not present evidence of a negative outcome that results from this practice, Pergamit and Veum (1999) showed that there are many positive consequences of promotion, such as an increase in supervisory responsibilities and the receipt of additional training. Other work has shown symptoms of age discrimination in labor markets.…”
Section: Historymentioning
confidence: 91%
“…For example, it may lead to greater training and supervisory responsibilities over other workers (for evidence on US workers, see Pergamit and Veum 1999). It may also move a worker from a temporary job to a permanent position within the ®rm or to a job whose earnings are based on bonuses and stock options.…”
Section: (Ii) Job Satisfaction Changesmentioning
confidence: 99%
“…Using the same data source over the period 1976±1988, McCue (1996 analyses the role and signi®cance of promotions and position changes, and examines the impact of promotions on wage growth. With samples drawn from the National Longitudinal Survey of Youth between 1989 and 1990, Pergamit and Veum (1999) investigate the determinants of a promotion among young workers and its consequences, in terms of subsequent wages, training and job attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Blacks typically have to exhibit substantial effort to "prove" themselves in predominantly white organizations where many are employed, particularly when desiring a promotion, given an authoritative position or seeking one (e.g. Kluegel 1978;Collins 1989;Baldi and McBrier 1997;Pergamit and Veum 1999;Smith 2005a, b). Thus, when layoffs reduce access to sources of social capital resources, the results of this study indicate that it could greatly affect them because of difficulty in developing many useful social relationships.…”
Section: Discussionmentioning
confidence: 99%